2019
DOI: 10.1016/j.ijms.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Sequential activation of methane by Ir+: An IRMPD and theoretical investigation

Abstract: The sequential activation of up to 4 CH4 molecules by Ir + is investigated through a gasphase infrared multiple photon dissociation (IRMPD) experiment and theoretical calculations. A molecular beam apparatus was used to generate Ir + by laser ablation and expose it to controlled amounts of CH4. Product ions were irradiated with IR light from a free electron laser over the 500-1800 cm-1 spectral range and photodissociation was monitored using a time-of-flight mass spectrometer. Experimental spectra were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…Products of these reactions were examined by infrared multiple photon dissociation (IRMPD) spectroscopy and assigned structures with the aid of quantum chemical calculations. Theoretical work builds from the Ta + + C2H6 reaction coordinate pathways investigated computationally by Lv et al [10] and the structures for [Ta,2C,4H] + examined by Simon et al [3] These results also extend our previous IRMPD studies of products formed in the reactions of 5d transition metal cations with hydrocarbons, which include M + + CH4 (M = Ta, W, Os, Ir, Pt) [6,12,13], and M + + x CH4 (x = 1 -4) (M = Ir, Pt) [14] [15].…”
Section: Introductionsupporting
confidence: 82%
“…Products of these reactions were examined by infrared multiple photon dissociation (IRMPD) spectroscopy and assigned structures with the aid of quantum chemical calculations. Theoretical work builds from the Ta + + C2H6 reaction coordinate pathways investigated computationally by Lv et al [10] and the structures for [Ta,2C,4H] + examined by Simon et al [3] These results also extend our previous IRMPD studies of products formed in the reactions of 5d transition metal cations with hydrocarbons, which include M + + CH4 (M = Ta, W, Os, Ir, Pt) [6,12,13], and M + + x CH4 (x = 1 -4) (M = Ir, Pt) [14] [15].…”
Section: Introductionsupporting
confidence: 82%
“…23,24 The main advantages of IRMPD spectroscopy over methods based on PID in other spectral regions [25][26][27][28][29][30][31] is that the IR spectral signatures allow the discrimination of functional groups, the analysis of conformational isomers and the identification of protonation/ coordination sites, especially when supported by theoretical calculations. 32,33 Consequently, IRMPD experiments have been used in an extensive number of systems and analytical applications, [34][35][36][37][38][39] from biomolecules, 40-42 drugs [43][44][45] and metabolites [46][47][48][49] to the evaluation of catalysis and reaction mechanisms, 19,[50][51][52][53][54][55][56] nanocalorimetry determinations 57,58 and in studies evaluating the electrospray ionization process 59 and aerosol composition. 60 Optical parametric oscillators (OPOs) coupled to optical parametric amplifiers (OPAs) deliver infrared radiation in the 2000-4500 cm −1 frequency range, allowing the evaluation of higher frequency modes such as O-H and N-H stretches.…”
Section: Introductionmentioning
confidence: 99%
“…to characterize ion-molecule reaction products. 51 , 52 A detailed IRMPD study of N 2 O decomposition on rhodium clusters by Mackenzie and co-workers revealed the influence of co-adsorbed oxygen. 53 However, even black-body infrared radiation is able to trigger N 2 O decomposition on small rhodium clusters, showing that no mode-specificity is involved.…”
Section: Introductionmentioning
confidence: 99%